199 Rates of Upper Extremity Compression Neuropathies Among Obese Patients Compared to Non-Obese Controls and Obese Patients Who Underwent Bariatric Surgery. (April 2023) - Khalid, Syed Ibad; Maasarani, Samantha; Thomson, Kyle; Pires, Giovanna; Becerra, Adan; Adogwa, Owoicho; Mehta, Ankit Indravadan; Noland, Shelley; Torquati, Alfonso
Abstract : INTRODUCTION: Upper extremity compression neuropathies(UECN) are increasingly prevalent and decrease the quality of life of affected individuals. Studies suggest obesity as a risk factor for carpal tunnel syndrome, the most common type of UECN. METHODS: A retrospective cohort study was conducted using the PearlDiver Mariner Database, an all-payor claims database containing claims for over 53 million patients from 2010 to 2019 in all 50 US states. Rates and odds of all types of UECN were compared between 1:1:1 exact matched cohorts of obese patients who were medically managed, obese patients who underwent bariatric surgery, and nonobese patients (111, 967 patients in each cohort). RESULTS: Compared with nonobese patients, patients with obesity were significantly more likely to develop any UECN (odds ratio [OR], 1.13; 95% confidence interval [CI], 1.09–1.18), carpal tunnel syndrome (OR, 1.15; 95% CI, 1.10–1.30), and 2 or more UECN (OR, 1.34; 95% CI, 1.20–1.48). Compared with obese patients who were managed medically, obese patients who underwent bariatric surgery were significantly less likely to develop any UECN (OR, 0.87; 95% CI, 0.84–0.91) and carpal tunnel syndrome (OR, 0.85; 95% CI, 0.81–0.89). CONCLUSIONS: Obese patients have higher odds of both single and concomitant UECN, specifically carpal tunnel syndrome, compared with nonobese patients. Bariatric surgery decreases the odds of developing UECN compared with obese patients not undergoing surgical intervention.